Hyperreality Found in a Short Story Set of Cinta Tak Pernah Sia-Sia by Agus Noor - Hasan Busro, Ahmad; Nuryatin, Agus; Setyaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The researcher chose the short story set of Cinta Tak Pernah Sia-SIa by Agus Noor because the short story had many hyperreality. Hyperreality refers to exaggerated false or new realities from the original ones. Hyperreality does not have any equivalence and looks more real and charming than the original ones. The researchers found these exaggerated realities in the short story set by Cinta Tak Pernah Sia-Sia by Agus Noor. This research aimed to determine the realizations of hyper-realities in the short story set of Cinta Tak Pernah Sia-Sia by Agus Noor. The applied approach was the post-modernism literature approach. This approach to hyperreality was proposed by Jean Baudrillard. In this research, the researchers found the realizations of hyper-realities, such as the figurations, the plots, and the story backgrounds. The results showed some hyperreality realizations of Cinta Tak Pernah Sia-Sia by Agus Noor. They were 1) the cockroach, 2) the cockroach's story plot, 3) the story atmosphere of the cockroach, 4) the cockroach queen, 5) the moon of Otok, 6) the moon, 7) the moon sale by Otok, 8) the famous and rich Otok, 9) the postcard, 10) Beningnya figure, 11) the story plot of the heaven postcard, and 12) the postcard of heaven.